2022
DOI: 10.1002/sce.21769
|View full text |Cite
|
Sign up to set email alerts
|

Connected epistemic practices in laboratory‐based engineering design projects for large‐course instruction

Abstract: In both K-12 and university settings, instructors and curriculum developers need to create learning experiences that provide students opportunities to engage in the disciplinary practices of science and engineering. However, instructional contexts pose challenges in developing such tasks. Using a framework focusing on conceptual and material epistemic practices and tools, we used a withinsubjects comparison to explore two different types of task designs, given realistic constraints posed by a largeenrollment u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…A focus on barriers and beliefs naturally emerges when fluency with technology is conceived in terms of knowledge acquired at the intersections between pedagogy, content, and technology— an instructor's technological pedagogical content knowledge (Archambault & Crippen, 2009; Harris et al, 2009; Voogt et al, 2013). Alternatively, we frame this issue in terms of practices , where practices are regularities in activity given meaning by and adapted to the contexts of their use (Forman, 2018; Koretsky et al, 2023; Wenger, 1998). In this section, we elaborate our practice‐based construct for the evolving ways and varying degrees to which instructors utilize educational technology (Graves & Bowers, 2018) and student‐centered pedagogical practices (Dancy et al, 2016; Indorf et al, 2021) and how these change over time—their trajectories of practice .…”
Section: Theoretical Framework: Trajectories Of Practicementioning
confidence: 99%
“…A focus on barriers and beliefs naturally emerges when fluency with technology is conceived in terms of knowledge acquired at the intersections between pedagogy, content, and technology— an instructor's technological pedagogical content knowledge (Archambault & Crippen, 2009; Harris et al, 2009; Voogt et al, 2013). Alternatively, we frame this issue in terms of practices , where practices are regularities in activity given meaning by and adapted to the contexts of their use (Forman, 2018; Koretsky et al, 2023; Wenger, 1998). In this section, we elaborate our practice‐based construct for the evolving ways and varying degrees to which instructors utilize educational technology (Graves & Bowers, 2018) and student‐centered pedagogical practices (Dancy et al, 2016; Indorf et al, 2021) and how these change over time—their trajectories of practice .…”
Section: Theoretical Framework: Trajectories Of Practicementioning
confidence: 99%
“…Participation in disciplinary practice entails "the activities of individual agents and group members that are necessary for a practice to achieve its aims" (Ford & Forman, 2006, p. 3). We categorize such participation according to conceptual, material, and social aspects (Koretsky et al, 2023) as briefly summarized in this section. As a launching point, we use scientific practices as they are articulated in the science studies literature, and then we connect each aspect to engineering practice.…”
Section: Aspects Of Disciplinary Practicementioning
confidence: 99%
“…The motivation to characterize shifts in social positioning stems from a systematic curricular change initiative where we have sought to redesign activities so that students engage in sociotechnical practices, practices where the technical and social aspects of engineering work are interrelated and mutually constitutive (Koretsky et al, 2018). We shift the emphasis from covering a canon of abstract content (often through solving constrained single correct-answer problems) to emphasizing the development of conceptual, material, and social practices of engineering (Ford & Forman, 2006;Koretsky et al, 2023;Trevelyan, 2019). This shift is primarily achieved by situating student work in realistic open-ended problems and providing appropriate instructor framing and facilitation (Koretsky et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this imagined Engineering World, as in the real world of engineering, engineering work comprises significant technical and social practices. Moreover, these two are “interlocked”—meaning that social practices influence the way engineers go about technical work, and vice versa (Gravel & Svihla, 2021; Koretsky et al, 2023). In short, tasks evoking Engineering World provide students the opportunity to use engineering principles and practices along with a diversity of perspectives to make progress on meaningful tasks.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The idea for our approach to task design in the middle years emerged from previous studies (Gilbuena et al, 2015;Hirshfield & Koretsky, 2021;Koretsky et al, 2014Koretsky et al, , 2015Koretsky et al, , 2023; we found that when teams of students in a final-year capstone course were given a realistic, complex design task to complete over 3 weeks, they productively and equitably engaged in the social and knowledge practices of chemical engineers. But little is known about whether tasks can be designed that effectively promote equitable disciplinary engagement in the middle years, where time is more limited, students' engineering knowledge needs to be developed, and engineering knowledge practices and social practices are not typically emphasized.…”
mentioning
confidence: 99%